2004
DOI: 10.1017/s1355617704105043
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of episodic memory deficits in neuropathologically-confirmed Dementia with Lewy bodies and Alzheimer's disease

Abstract: Little is known about possible differences in the memory deficits that occur in Dementia with Lewy bodies (DLB) and Alzheimer's disease (AD). We compared 24 autopsy-confirmed DLB and 24 age-, education-, and MMSE-matched autopsy-confirmed AD patients on the California Verbal Learning Test (CVLT) and the Wechsler Memory Scale-Revised Logical Memory subtest. The DLB and AD groups were similarly impaired on CVLT Total Learning (Trials 15) and Long Delayed Free Recall, but the DLB group demonstrated relative impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 48 publications
4
70
1
1
Order By: Relevance
“…These findings are consistent with other preliminary reports in the literature. 47 Pure DLB participants performed significantly better on all tests of verbal memory than did pure AD or mixed DLB/AD participants. Further, the DLB/AD performance was roughly equivalent to the AD participants on the verbal composite score and its subtests, indicating that LB and AD neuropathologic burden did not produce worse verbal memory in the combined group.…”
mentioning
confidence: 78%
“…These findings are consistent with other preliminary reports in the literature. 47 Pure DLB participants performed significantly better on all tests of verbal memory than did pure AD or mixed DLB/AD participants. Further, the DLB/AD performance was roughly equivalent to the AD participants on the verbal composite score and its subtests, indicating that LB and AD neuropathologic burden did not produce worse verbal memory in the combined group.…”
mentioning
confidence: 78%
“…Thus, heterogeneous pathological processes may exist in MCI patients, who then experience different cognitive dysfunction patterns. Different cognitive profiles are also associated with different prognoses, with episodic memory impairment regarded as a predictor of development of AD [35,39,40], whilst working memory impairment is more strongly associated with the onset of other types of dementia, such as vascular dementia and Lewy body dementia [41,42,43,44,45]. …”
Section: Discussionmentioning
confidence: 99%
“…This was shown in a study that directly compared the performance of patients with autopsy-confirmed DLB (all with concomitant AD pathology) or with pure AD on the CVLT and the WMS-R logical memory test (Hamilton et al 2004). Although the two groups were equally impaired in their ability to learn new verbal information on these tests, the DLB patients exhibited better retention and better recognition memory than patients with pure AD.…”
Section: Alzheimer Disease Versus Dementia With Lewy Bodiesmentioning
confidence: 92%